Catholiques Chinois - Moncay, Tonkin - Cartepostalesale 02 - Uncredited photographer. (Wikimedia Commons, 1945)
Carte postale ancienne issue de Wikimedia Commons. Titre: Catholiques Chinois - Moncay, Tonkin - Cartepostalesale 02. A postcard depicting Chinese members of the Roman Catholic Church in the Tonkinese city of Móng Cái, Hi Ninh Province.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale